The Influence of Macroeconomic Variables on Asean- 5 Countries’ Foreign Exchange Reserves Long-Term Relationship and Causality (Empirical Data Year 2014 to 2021): - Roosaleh Laksono; Dewabrata, Ignatius Oki; Kartadjumena, Eriana; Serlita, Erly; Bayunitri, Bunga Inda (Technium EconomiA, 2024)
The country’s foreign exchange reserves are an important factor in supporting the economic development process in ASEAN-5 countries. The country’s foreign exchange reserves are greatly influenced by macroeconomics so macroeconomic changes will have a large and rapid impact on foreign exchange reserves. So this research aims to determine the influence of macroeconomics, namely the rate of inflation, exchange rate, export value, and economic growth on the foreign exchange reserves of ASEAN-5 countries. The data processing was carried out using the multiple panel data regression method, empirical data from 2014 to 2021. The results of the data processing that has been carried out show that the model test, together with the inflation rate, exchange rate, export value, and economic growth, has an effect of 94.9867 percent. to the foreign exchange reserves of ASEAN-5 countries. Meanwhile, partially the export value and economic growth variables have a significant effect on ASEAN countries’ foreign exchange reserves and are positively proportional, but the inflation rate and exchange rate have no effect on ASEAN countries’ foreign exchange reserves and are negatively proportional. Apart from that, the role of the government is also very influential in maintaining the country’s foreign exchange reserves because macroeconomics is determined by government policies.